T Cell Subsets and the Expression of Related MicroRNAs in Patients with Recurrent Early Pregnancy Loss - Ya-ni Yan; Jian Zhang; Na Yang; Chaochao Chen; Weiwei Li (Mediators of Inflammation)
This study explored the role of T cell subsets and the expression of related microRNAs in patients with recurrent early pregnancy loss (EPL). Fifty patients with EPL loss between May 2018 and May 2021 were randomly selected as the EPL group, and 50 pregnant women with normal pregnancies or normal delivery outcomes were randomly selected as the control group. The expression levels of T cell subset-related markers and T cell subset-related miRNAs, in addition to the frequencies of T cell subsets, in peripheral blood of the two groups were analyzed. In terms of T cell-related markers, the results showed that the expression levels of the transcriptional regulator TBX-21 (T-bet) and interferon regulatory factor 4 (IRF4) were significantly upregulated in peripheral blood of the patients in the EPL group (P<0.05), whereas the expression levels of GATA binding protein 3 (GATA3) and glucocorticoid-induced tumor necrosis factor receptor (GITR) were significantly downregulated (P<0.05). In the EPL group, the expression of mir-106b, mir-93, and mir-25 was upregulated (1.51±0.129, 1.43±0.132, and 1.73±0.156, respectively) in regulatory T (Treg) cell-related T cell subsets, whereas the expression of miR-146a and miR-155 was downregulated (P<0.05). The frequencies of Treg and exhausted T cells in the EPL group were significantly lower than those in the control group (P<0.05). The cell frequencies of T helper 17 (Th17) cells and exhausted Treg cells in the EPL group were significantly higher than those in the control group (P<0.05). In conclusion, immune cells and associated miRNA profiles can be used as prognostic biomarkers for the treatment of human reproductive disorders, such as EPL.